Pengembangan Sistem Aplikasi Transaksi Bank Sampah Online Berbasis Web (Studi Kasus : Bank Sampah Malang) - Meilisa Dwiyati Marali; Fajar Pradana; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Bank Sampah Malang (BSM) is a foundation with focus in collecting and processing waste from activities revolve around Malang. One of the activities in BSM included making savings from the waste that still can be sold. From the transaction, there are several problems felt by both the officers and customers of BSM. First problem is the officers of BSM need a medium to introduce BSM to society, especially in Malang. They also found it is hard to locate the customers that used a ‘pick-up waste' service. Second problem from the customer used the ‘pick-up waste' service, in which, the system used is troublesome. Their saving books have to be brought by the officer to be checked by teller, and they have to pick their saving books in BSM office next day. The purpose of this research is to help BSM to create a web-based online transaction to help solving the problem stated above. The software development in this research is done by using Waterfall method. Stages performed in this research include literature research, analysis of user needs, System Design, implementation, testing, and decision making. This system is developed in web-based environment and the programming language used is PHP. Google Maps API is used to read and locate the pick-up location. Unit testing use white box method and the result is 100% valid in 3 testing cases. The validation testing use blackbox method and the result is 100% valid from 32 testing cases. Compatibility's testing result also shown 100% valid from 3 testing cases.